Chemical and visual characterisation of EGRIP glacial ice and cloudy bands within - Stoll N.; Westhoff J.; Bohleber P.; Svensson A.; Dahl-Jensen D.; Barbante C.; Weikusat I. (The Cryosphere, 2023)
Impurities in polar ice play a critical role in ice flow, deformation, and the integrity of the ice core record. Especially cloudy bands, visible layers with high impurity concentrations, are prominent features in ice from glacial periods. Their physical and chemical properties are poorly understood, highlighting the need to analyse them in more detail. We bridge the gap between decimetre and micrometre scales by combining the visual stratigraphy line scanner, fabric analyser, microstructure mapping, Raman spectroscopy, and laser ablation inductively coupled plasma mass spectrometry 2D impurity imaging. We classified approximately 1300 cloudy bands from glacial ice from the East Greenland Ice-core Project (EGRIP) ice core into seven different types. We determine the localisation and mineralogy of more than 1000 micro-inclusions at 13 depths. The majority of the minerals found are related to terrestrial dust, such as quartz, feldspar, mica, and hematite. We further found carbonaceous particles, dolomite, and gypsum in high abundance. Rutile, anatase, epidote, titanite, and grossular are infrequently observed. The 2D impurity imaging at 20μm resolution revealed that cloudy bands are clearly distinguishable in the chemical data. Na, Mg, and Sr are mainly present at grain boundaries, whereas dust-related analytes, such as Al, Fe, and Ti, are located in the grain interior, forming clusters of insoluble impurities. We present novel vast micrometre-resolution insights into cloudy bands and describe the differences within and outside these bands. Combining the visual and chemical data results in new insights into the formation of different cloudy band types and could be the starting point for future in-depth studies on impurity signal integrity and internal deformation in deep polar ice cores.